The Leadership Style of Kiai Manshur in Forming Anfa’linnas Students: Case Study at Pondok Pesantren Tahfidz Yanbu'ul Qur'an Menawan - Muhammad Rizki Al Mubarok; Much Imron (Journal of Management and Entrepreneurship Research, 2020)
Objective: This study explores the characteristics and leadership style of kiai (boarding school leader and Islamic teacher) Manshur as a leader in the pondok pesantren (Islamic boarding school) that he fostered. Kiai Manshur’s leadership traits are also explored in this study in detail with in-depth analysis. Research Design & Methods: Several qualitative approaches were used to collect information about Kiai Manshur, including direct observation, questionnaires, in-depth interviews, and documentation. Technically, involve themselves and interact directly in the activities carried out by Kiai Manshur. The information is analyzed interactively, data reduction, data display, and drawing conclusions. Findings: The results of this study indicated that Kiai Manshur uses a special compilation in leading his pondok pesantren to form a distinctive leadership style. The style created the his leadership characteristics, including integrity, discipline, competence, trustworthiness, humanism, communication, and organizational. The leadership style of Kiai Manshur aims to produce anfa’linnas santri (good and helpful student). Implications & Recommendations: There is no perfect writing, but the limitations do not reduce the quality of the results study. Further research can discuss more about the anfa’linnas students, characteristics and effectiveness of application in the society. Contribution & Value Added: The results of this study provide a scientific contribution to leadership in organizations, especially in non-profit organizations such as Islamic boarding schools (traditional educational institutions) and the concept of anfa’ linnas student. Practically, the board of Islamic boarding schools and teachers can use these findings as material to develop the institution for the benefit of many people.